How I Got Pregnant: Should Having a Child Justify a Partner’s ‘Deception’? - Haidar, Hazar (BioéthiqueOnline, 2016)
This is a commentary related to the creative work by James Dwyer entitled “How I Got Pregnant”, a story that raises ethical issues about a woman’s request for medical assistance to get pregnant without the intention to disclose this to her husband. In this commentary, I argue that this woman’s attitude breaks trust with her husband, and show why the justifications she offered in order to argue for her request to conceive a child without her husband’s knowledge are flawed.